Game-Related Statistics in the Spanish Water Polo League: Differences between Seasons (Estadísticas de partido en la Liga Española de Waterpolo: Diferencias entre temporadas) - Iglesias Pérez, María del Carmen; García Ordóñez, Enrique; Touriño González, Carlos (Retos, 2018)
The aim of this study was to identify the differences between seasons in men´s water polo regular competition by analysing the changes of game-related statistics. The sample comprised 88 games from the Spanish Professional Water Polo League (2011-2014). The game-related statistics were clustered into five groups: attacks in relation to the different playing situations, shots in relation to the different playing situations, attacks outcome, origin of shots and technical execution of shots. Univariate (ANOVA, Kruskal-Wallis and Generalized Linear Model tests) and multivariate (Discriminant) analyses were used to compare seasons, and statistical significance and effect sizes of the differences between seasons were calculated for the game-related statistics. The data were compositional data, therefore the variables were modified with additive log-ratio transformation. During the 2011-2012 season, the teams had significantly higher averages in even attacks (p<.01) and shots from zone 3 (p<.05). In the 2013-2014 season, teams had significantly higher averages in counterattack (p<.001), counterattack shots (p<.01), shots from zone 6 (p<.05) and 4 (p<.05). The variables that best distinguished between seasons were counterattack shots, counterattack, shots from zone 6 and 3, and even attacks. The group that best discriminated among seasons was “Origin of shots” (46.5% original sample and 42.3% cross-validation). The increase in counterattacks and in zone 6 shots seems to indicate a trend towards faster games and greater relevance of the centre forward. These findings can contribute to a better understanding of the evolution of water polo performance indicators, helping the coaches to prepare the players accordingly. Resumen: El objetivo de este estudio fue identificar las diferencias entre temporadas para las estadísticas de juego en waterpolo masculino. La muestra consistió en 88 partidos de la Liga Española de Waterpolo (2011-2014). Las estadísticas de juego fueron agrupadas en cinco grupos: ataques según las diferentes situaciones de juego, lanzamientos según las situaciones de juego, resultado del ataque, origen de lanzamiento y ejecución técnica de lanzamiento. Se aplicaron varios métodos estadísticos, univariantes (ANOVA, Kruskal-Wallis y Modelo Lineal Generalizado) y multivariantes (análisis discriminante) para comparar las estadísticas entre las diferentes temporadas, calculándose diferencias significativas y tamaños del efecto. Debido a la existencia de datos composicionales, las variables fueron transformadas utilizando la función log-cociente aditiva. Se observó que durante la temporada 2011-2012 los equipos realizaron más ataques en igualdad (p<.01) y lanzamientos desde zona 3 (p<.05). En la temporada 2013-2014, realizaron más contraataques (p<.001), lanzamientos en contraataque (p<.01) y lanzamientos desde zona 6 (p<.05) y 4 (p<.05). Las variables que mejor discriminaron entre temporadas fueron los contrataques, lanzamientos en contrataque, lanzamientos de zona 6 y 3, y ataques en igualdad. El grupo que mejor discriminó entre temporadas fue “Origen de lanzamiento” (46,5% muestra original y 42,3% validación cruzada). El aumento de contraataques y lanzamientos de zona 6 parecen indicar una tendencia hacia juegos más rápidos y mayor relevancia del boya. Estos hallazgos pueden contribuir a mejorar el conocimiento de la evolución de los indicadores de rendimiento en waterpolo, ayudando a los entrenadores para preparar a sus jugadores de acuerdo a estos cambios.